Sustainable Development Goals and Human Rights - Kaltenborn, Markus; Krajewski, Markus; Kuhn, Heike; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This open access book analyses the interplay of sustainable development and human rights from different perspectives including fight against poverty, health, gender equality, working conditions, climate change and the role of private actors. Each aspect is addressed from a more human rights-focused angle and a development-policy angle. This allows comparisons between the different approaches but also seeks to close gaps which would remain if only one perspective would be at the center of the discussions. Specifically, the book shows the strong connections between human rights and the objectives of the 2030 Agenda for Sustainable Development and the Sustainable Development Goals adopted by the United Nations in 2015. Already the preamble of this document explicitly states that (3z(Bthe 17 Sustainable Development Goals ... seek to realise the human rights of all(3y(B. Moreover, several goals and targets of the 2030 Agenda correspond to already existing individual human rights obligations. The contributions of this volume therefore also address how the implementation of human rights and SDGs can reinforce each other, but also point to critical shortcomings of the different approaches.s
Introduction -- How Can a Human Rights-Based Approach Contribute to Poverty Reduction? The Relevance of Human Rights to Sustainable Development Goal One -- The Human Rights Framework for Establishing Social Protection Floors and Achieving Universal Health Coverage -- People and Their Health Systems: The Right to Universal Health Coverage and the SDGs in Africa -- Freedom from Violence, Full Access to Resources, Equal Participation, and Empowerment: The Relevance of CEDAW for the Implementation of the SDGs -- SDGs, Gender Equality and Women$1 (Bs Empowerment: What Prospects for Delivery? -- Superfluous Workers: Why SDG 8 Will Remain Elusive -- Reducing Inequality Within and Among Countries: Realizing SDG 10$1 (BA Developmental Perspective -- Securitizing Sustainable Development? The Coercive Sting in SDG 16 -- Climate Change, Sustainable Development, and Human Rights -- Reflecting on the Right to Development from the Perspective of Global Environmental Change and the 2030 Agenda for Sustainable Development -- The Role of Public and Private Actors and Means in Implementing the SDGs: Reclaiming the Public Policy Space for Sustainable Development and Human Rights -- Towards a Division of Labour for Sustainable Development: Extraterritorial Human Rights Obligations.s
Keywords: Human rights; Economic development; Sustainability; Climatology; Human Rights; Development Studies; Sustainability; Climate Sciences